Nanopartículas contendo propionato de clobetasol: preparação, caracterização e incorporação em hidrogéis - Fontana, Márcia Camponogara (2010)
The aim of this work was the development of nanostructured formulations containing clobetasol propionate. Initially, it was validated a chromatographic method to assay clobetasol propionate in nanocapsule suspensions. Clobetasol propionate-loaded nanocapsules and nanospheres of poly(ε-caprolactone) (PCL) and nanoemulsion (0.5 mg mL-1) were prepared by the interfacial deposition of preformed polymer method, nanoprecipitation and spontaneous emulsification, respectively. Formulations were characterized by means of drug content, encapsulation efficiency, pH, mean size, polydispersity index, zeta potential, morphology analysis, and stability under storage. The PCL nanocapsules showed the highest physicochemical stability, followed by the nanoemulsions and nanospheres. In the evaluation of in vitro release of clobetasol propionate, the nanocapsules showed a better control of drug release, according to the biexponential model. The photodegradation study of clobetasol propionate against UVA light showed the importance of the polymer and the oil in the nanoparticles to protect the drug from light. From these results, the nanocapsules were chosen for the study of the influence of the polymerid material on the physicochemical stability umder storage, photostability, release profile of the drug and its release mechanism. The nanocapsules prepared with poly(lactide) (PLA) showed a higher stability in comparison to the nanocapsules prepared with poly(lactide-co-glycolide) 50:50 and 85:15, although its stability was lower than nanocapsules prepared with PCL. Photodegradation studies demonstrated the pretection of the nanoencapsulated drug, regardless of the polymeric material of the nanocapsule s wall. The in vitro release study demonstrated the controlled release of the drug according to an anomalous transport. Due to these results, the nanocapsules prepared with PCL were selected for the development and preparation of hydrogels. Similar formulations containing nanospheres and nanoemulsion were used to evaluate the influence of polymer and oil on different properties of the hydrogels. These dosage forms were evaluated for drug content, pH, spreadability, rheology and in vitro drug release. All hydrogels presented properties compatible to the topical application. The presence of the drug-loaded nanoparticles in hydrogels led a slower drug release, especially for the formulation containing nanocapsules. The drug release profile was according to the Higuchi model.